Math, asked by tulasilaxmikandrekul, 4 months ago

A function is given by f(x) =3x + 5 then f(-1) =​

Answers

Answered by anupama1568
1

Answer:

f( - 1) = 3( - 1) + 5 \\  \: - 3 + 5 \\  \: 2

I hope it help you....

Answered by thaththai2006
0

Answer:

f-1(x) = x/3 + 5/3

Step-by-step explanation:

The inverse function is found by replacing the independent variable with the dependent variable and vice versa like so

 

f(x) = 3x-5 becomes x = 3y-5; now we solve for y

 

3y = x +5 or y = x/3 + 5/3

 

Therefore the inverse function becomes: f-1(x) = x/3 + 5/3

Mark My Answer As the Brainliest...

Similar questions